A Captured Adult Female Mantis Religiosa (Insecta: Mantodea) Laid Four Oothecas under Laboratory Conditions: An Observational Approach - Turaman, Cem (New Visions in Biological Science Vol. 5, 2021)
For its numerous spectacular features, the Mantodea (Insecta) (Burmeister, 1838) is a well-studied insect. However, according to the author's knowledge, the number of oothecas laid by a female Mantis religiosa (Linnaeus, 1758) has not been reported. Between September and October 2019, a captured female Mantis religiosa was reared in the laboratory of Hacettepe University, Faculty of Biology, Department of Forensic Entomology, Ankara, Turkey. The objective of this study is to roughly determine the number of oothecas laid by a female Mantis religiosa. During her captivity, this female has produced four oothecas. When offspring develop from these oothecas, they can be artificially selected to be reared as biological control agents.